The carbon footprint of Brazilian households through the Consumer Expenditure Survey (POF) - Cachola, Celso da Silveira (2021)
The main objective of this article is to assess the carbon footprint of Brazilian families based on the Household Expenditure Survey (POF), 2008-2009, from the Brazilian Institute of Geography and Statistics (IBGE). The methodology used to quantify the Brazilian households’ carbon footprint has comprised three data sources: i) Household expenditure Survey, 2008-2009; ii) Leontief matrix of Brazilian accounts, year 2010; and iii) 2009 World Input-Output Database (WIOD) environmental inventory. Initially, an input-output (IO) model was created. Next, the results from the IO model were combined with the information of the POF. The poorest families, with a monthly income of up to $ 415.00, emit less than 1.5 metric tons per year, in contrast, the wealthiest families, with a monthly income above $ 5,187.50, release around 18.5 tons, almost 12 times more. It was found that an increase in income, results in an increase in CO2eq emissions. Thus, while the poorest families, which represent more than 20% of the total Brazilian families, cause 7% of the total emissions, the wealthiest families cause 16% of the total emissions although they represent only 4% of the total families. It was observed that the food category loses importance as income increases, while the opposite occurs in the services category. For the poorest families, there is great importance in the housing category, mostly caused by the consumption of electricity and LPG. Therefore, important measures for economic growth supported by actions become particularly relevant.